(untitled) (Economics and region, 2020)
The importance of high-tech production in the stability of the economy of Аzerbaijan. The aim of this research is a theoretical and empirical study of the role of high-tech production in the sustainability of the economies, particularly Azerbaijani economy. The methodology of the paper lies in the fundamental works of foreign scientists and United Nations research in the field of determining and assessing the sustainability of the economic system. As a result of the study, the significance and structure of low, medium and high-tech production in Azerbaijan were determined. On the basis of a critical analysis of the scientific literature on this topic and the results obtained, the article proposed relevant proposals and conclusions. The data obtained in this article is relevant and can be used to monitor the economy and increase in its sustainability. The main factor in the sustainability of the economy was determined to be the share and effectiveness of high-tech products in the structure of industrial production. The proposed measures will lead to an increase in the stability of the Azerbaijani economy, a decrease in the fluctuation in dynamics of macroeconomic indicators, which ultimately will lead to an increase in the growth rate of GDP per capita and sustainable economic growth in the long term.